Human Gamma-Thrombin: Lack of Correlation Between a Platelet Functional Response and Glycoprotein V Hydrolysis - Jandrot-Perrus, Martine; Guillin, Marie-Claude; Nurden, Alan T (Thrombosis and Haemostasis, 1987)
The ability of purified human gamma-thrombin to stimulate platelet function was related to its capacity to degrade GP V. Compared to alpha-thrombin, much greater amounts of gamma- thrombin were required to induce platelet aggregation; and this also applied to secretion from dense bodies, alpha-granules and lysosomal granules. Platelet stimulation by gamma-thrombin was additionally characterized by the presence of a lag-phase. Platelets with 3H-labelled surface glycoproteins showed the same functional response to both alpha- and gamma-thrombin as unlabelled platelets. But while threshold levels of alpha-thrombin induced little GP V hydrolysis confirming McGowan et al. (1), amounts of gamma-thrombin which induced substantial degradation (e. g. 8.3 nM degraded 36% of platelet GP V in 3 min) were unable to sustain either platelet aggregation or secretion. These results suggest that protein-binding regions remote from the catalytic site of alpha-thrombin are more important for platelet activation than GP V hydrolysis. They also provide further support to the argument that GP V hydrolysis may not be the essential trigger of platelet activation by thrombin.
Keywords: Platelet aggregation; Platelet secretion; GP V hydrolysis; Human alpha-thrombin; Human gamma-thrombin